PROSES DISEMINASI CORE SAMPLER KEPADA PETANI TEBU RAKYAT DI PG BUNGAMAYANG - Trikuntari Dianpratiwi; Triantarti Triantarti; Syukur H.K. (Universitas Sebelas Maret, 2016)
Core sampler (CS) is a tool to get indivual cane sample on the truck to determined rendement. Dissemination process of CS in Bungamayang SF on 2014 had focussed by: (1) application concept of individual system by determine the CS on first step (transition step), and (2) socialization to cane farmer about awareness of individual rendement system, to get the cane farmers responses to determie individual rendement by CS. The aim of the dissemination is do socialization to the farmer about rendement determine system by CS. The steps of the socialization are socialization of rendement determine system by CS to SF’s staff and cane farmers before milling season; to set the application concept of CS determine rendement individual system; assistance and evaluation. Socialization had done to the cane farmers at Bungamayang SF, the responses had measured by quesionare at step socialization and had analyzed descriptifly. The number of truck had evaluated are 4.947. The meeting with farmer group coordinator, staff of agricultural division, and managers of pabrikasi agree that determine of CS individual rendement system had applicated as base of payment to farmer at 2014 milling season. The 62,64% of respondent agreed with rendement that they reach, because corresponding with cane agricultural that they done, the figure of cane had been harvested, and the rendement is higher than milling season before. Rejection of CS’s rendement is 37,36%, because they feel that they was done the good agricultural and they know that the miller often trouble. The way of the farmer group chairman deliver explanation about rendement was correct: to motivate cane farmer to revise agricultural so that reach higher rendement (38,49%) and rendement fix to the quality of cane (22,64%). The result of socialization show that cane farmer at Bungamayang SF know the fuction of CS, the work of CS, and CS system is worthy to solve the problem of rendement measurement.